These two lines create vertical angles, which are congruent. That means angle z = 60 degrees. Since angle z and the angle represented by the expression 6x + 60 are supplementary (they are adjacent angles that add to equal 180 degrees), you can set up the following equation to find x:
6x + 60 + 60 = 180
6x + 120 = 180
6x = 60
x = 10
Answers:
x = 10
z = 60
Answer:
-3x^{4} + 19x^{3} - 38x^{2} + 25x - 3
Step-by-step explanation:
1) distribute x² into (-3x² + 7x - 1) to get: -3x^{4} + 7x³ - x²
2) distribute -4x into (-3x² + 7x - 1) to get: 12x³ - 28x + 4x
3) distribute 3 into (-3x² + 7x - 1) to get: -9x² + 21x - 3
4) combine all the answers together into one equation:
-3x^{4} + 7x³ - x² + 12x³ - 28x² + 4x - 9x² + 21x - 3
5) combine like terms:
7x³ + 12x³ = 19x³
-x² + -28x² + -9x² = -38x²
4x + 21x = 25x
6) combine answers together into one equation:
-3x^{4} + 19x³ - 38x² + 25x - 3
Since a(n)=-3(a(n-1)) the common ratio is -3, and a(1)=-3 so
a(n)=-3(-3^(n-1)) so the first four terms are:
-3, 9, -27, 81
Answer:
3
Step-by-step explanation:
Same as: 8.5-5.5 = 3
Answer: 510
Step-by-step explanation: